Molecular Profiling Defines Distinct Prognostic Subgroups in Childhood AML: A Report From the French ELAM02 Study Group. Issue 1 (January 2018) - Marceau-Renaut, Alice; Duployez, Nicolas; Ducourneau, Benoît; Labopin, Myriam; Petit, Arnaud; Rousseau, Alexandra; Geffroy, Sandrine; Bucci, Maxime; Cuccuini, Wendy; Fenneteau, Odile; Ruminy, Philippe; Nelken, Brigitte; et al.
Abstract : Abstract: Despite major treatment improvements over the past decades, pediatric acute myeloid leukemia (AML) is still a life-threatening malignancy with relapse rates up to 30% and survival rates below 75%. A better description of the pattern of molecular aberrations in childhood AML is needed to refine prognostication in such patients. We report here the comprehensive molecular landscape using both high-throughput sequencing focused on 36 genes and ligation-dependent RT-PCR in 385 children with de novo AML enrolled in the prospective ELAM02 trial and we evaluated their prognostic significance. Seventy-six percent of patients had at least 1 mutation among the genes we screened. The most common class of mutations involved genes that control kinase signaling (61%) followed by transcription factors (16%), tumor suppressors (14%), chromatin modifiers (9%), DNA methylation controllers (8%), cohesin genes (5%), and spliceosome (3%). Moreover, a recurrent transcript fusion was detected in about a half of pediatric patients. Overall, CBF rearrangements, NPM1 and double CEBPA mutations represented 37% of the cohort and defined a favorable molecular subgroup (3 years OS: 92.1%) while NUP98 fusions, WT1, RUNX1, and PHF6 mutations (15% of the cohort) segregated into a poor molecular subgroup (3 years OS: 46.1%). KMT2A -rearrangements (21% of the cohort) were associated with an intermediate risk. Despite some overlaps, the spectrum of molecular aberrations and their prognostic significance differ between childhood and adult AML. These data have important implications to contribute in refining risk stratification of pediatric AML and show the need for further validations in independent pediatric cohorts. Abstract : Supplemental Digital Content is available in the text